Efektivitas Pembelajaran Berbasis Digital Ditinjau Dari Hasil Belajar Matematika Siswa Kelas VIII SMP Negeri 2 Baubau - Artati Iriana; Rismayani Armin; Haidir Ali (Jurnal Akademik Pendidikan Matematika, 2023)
The purpose of this research was to see the effectiveness of digital-based learning in terms of the mathematics learning outcomes of class VIII students of SMP Negeri 2 Baubau. This research uses a quantitative approach with a quast-experimental type of research. The population in this study were all class VIII students of SMP Negeri 2 Baubau which were spread over 11 classes. The sample used is a saturated sample, because the existing population has homogeneus learning outcomes, then the sample is taken in two classes, namely class VIII.2 and class VIII.3. Data collection technique in this study use tests. The result of the research is that the significance value is 0.028, the N-Gain value is obtained from the difference in the average value of mathematics learning outcomes for experimental class students of 66.93 and control class of 57.10. Then the effectiveness criteria are based on the gain score, the percentage of the experimental class is 66.93% which is included in the quite effective category because it is between 56% to 75%, then H0 is rejected and H1 is accepted based on the hypothesis acceptance criteria, this means that the application of digital-based learning is quite effective in terms of the mathematics learning outcomes of class VIII SMP Negeri 2 Baubau on the subject of statistics.